The green economy and inequality in Sub-Saharan Africa: Avoidable thresholds and thresholds for complementary policies - Simplice A Asongu; Nicholas M Odhiambo (Energy Exploration & Exploitation, 2021)
The study examines nexuses between carbon dioxide (CO 2 ) emissions, renewable energy consumption and inequality in 39 Sub-Saharan African countries for the period 2004–2014. The empirical evidence is based on Quantile regressions. First, in the 25th quantile of the inequality distributions, as long as CO 2 emissions metric tons per capita are kept below 4.700 (4.100), the Gini coefficient (Atkinson index) will not increase. These are avoidable CO 2 emissions thresholds. Second, renewable energy consumption should be complemented with other policies to: (i) reduce the Gini coefficient when renewable energy consumption is at 50.00% of total final energy consumption and (ii) mitigate the Atkinson index when renewable energy consumption is at 62.500% of total final energy consumption in the bottom quantiles of the Atkinson index distribution and at 50.00% of total final energy consumption in the 75th quantile of the Atkinson index distribution. These are renewable energy consumption thresholds for complementary policies. The novelty of this study in the light of extant literature is fundamentally premised on providing policy makers with avoidable thresholds of CO 2 emissions as well as corresponding thresholds of renewable energy consumption for complementary policies, in the nexus between the green economy and inequality.